2015
DOI: 10.1007/s12010-015-1752-6
|View full text |Cite
|
Sign up to set email alerts
|

A New Subtilase-Like Protease Deriving from Fusarium equiseti with High Potential for Industrial Applications

Abstract: A gene encoding a novel extracellular subtilisin-like protease was cloned from the ascomycete Fusarium equiseti and expressed in Trichoderma reesei. The F. equiseti protease (Fe protease) showed excellent performance in stain removal and good compatibility with several commercial laundry detergent formulations, suggesting that it has high potential for use in various industrial applications. The recombinant enzyme was purified and characterized. The temperature optimum of the Fe protease was 60 °C and it showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…F. equiseti is also employed as a plant growth promoting fungus (82,83). Also, an F. equiseti-dreived protease showed excellent stain removal property and was compatible with several commercial laundry detergent formulations (85).…”
Section: Discussionmentioning
confidence: 74%
“…F. equiseti is also employed as a plant growth promoting fungus (82,83). Also, an F. equiseti-dreived protease showed excellent stain removal property and was compatible with several commercial laundry detergent formulations (85).…”
Section: Discussionmentioning
confidence: 74%
“…With respect to mercury at 200 mg/L there was total inhibition of fungus growth for TCH 1 and 2 whereas for TCH 3, 4 and 5 the growth started only after 60 hours and with noticeable effect of mercury retarding both growth and sporulation. Also, Juntunen et al (2015) showed that at optimum temperature, Fe protease showed high activity in the pH range of 6-10, with a sharp decline in activity at pH above 9.0.…”
Section: Discussionmentioning
confidence: 96%
“… Unprimed Subsites Primed Subsites Microorganism Classification S 5 S 4 S 3 S 2 S 1 S ’ 1 S ’ 2 S ’ 3 S ’ 4 S ’ 5 Substrate Ref. Fusarium equiseti Subtilase-like ND Asn Gly Thr His Tyr Gly Lys Gly ND Hydrolysis profile of the β-casein, cytochrome c and ubiquitin [ 18 ] Aspergillus fumigatus Sedolisin (SedA) ND ND ND ND ND ND ND ND ND ND Resorufin-labeled casein [ 19 ] Talaromyces emersonii Prolyl aminopeptidases ND ND ND ND Pro ND ND ND ND …”
mentioning
confidence: 99%